Design and Development of Raw Material Inventory System for “Es Barbar” SME Using the Material Requirement Planning Method - Arsydi, Mohammad Dandi; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
The difficulty in managing raw material inventory has become a major challenge for the UMKM Es Barbar, leading to imbalances such as shortages or excess materials, which hinder operational smoothness. This study aims to design and develop a web-based information system using the Material Requirement Planning (MRP) method to improve raw material management efficiency. With the System Development Life Cycle (SDLC) approach using the waterfall model, the system was designed through stages of communication, planning, modeling, construction, and implementation. The results show that the application of the MRP method successfully reduced stock shortages by 95% and excess stock by 85%, as well as improved the accuracy of raw material planning based on the Master Production Schedule (MPS) and Bill of Materials (BOM). This system facilitates precise raw material requirement planning, supports decision-making, and reduces waste, there by having a positive impact on the operational efficiency of UMKM Es Barbar.